Pemberdayaan Masyarakat Melalui Pengembangan Desa Wisata: Studi Deskriptif di Desa Dayun - Ranti Nurcahaya; M. Jaya Adi Putra; Dafetta Dafetta Fitrilinda (Jurnal Diferensiasi: Jurnal Hasil Penelitian, Pengembangan dan Kajian Kepustakaan di Bidang Pendidikan, 2026)
Abstract: Community empowerment is a strategic approach for strengthening rural capacity, local economic independence, and sustainable tourism governance. This study aims to describe community empowerment through the development of Dayun Tourism Village in Dayun District, Siak Regency, Riau Province. The study employed a qualitative descriptive design. Data were collected through observation, documentation, and interviews with two key informants and one supporting informant representing the village apparatus, tourism village manager, and local entrepreneur. The analysis focused on four empowerment dimensions: social, economic, cultural, and environmental. The findings show that the development of Dayun Tourism Village has encouraged community participation through Tourism Awareness Group activities, tourism-service training, local business initiatives, and the use of the integrated reservoir as an educational and recreational attraction. Economically, the program has created opportunities for micro-enterprises, local food processing, homestays, guiding services, and creative products such as watermelon-themed batik and processed watermelon products. Culturally, tourism development has strengthened the visibility of Malay arts, local hospitality, and village identity. Environmentally, the program has promoted public awareness of cleanliness, water-resource management, and conservation-oriented use of village assets. The study concludes that tourism village development can serve as an effective empowerment strategy when the community is positioned not only as beneficiaries but also as active actors in planning, management, and evaluation. Abstrak: Pemberdayaan masyarakat merupakan pendekatan strategis untuk memperkuat kapasitas warga, kemandirian ekonomi lokal, dan tata kelola pariwisata berkelanjutan. Penelitian ini bertujuan mendeskripsikan pemberdayaan masyarakat melalui pengembangan Desa Wisata Dayun di Kecamatan Dayun, Kabupaten Siak, Provinsi Riau. Penelitian menggunakan pendekatan deskriptif kualitatif. Data dikumpulkan melalui observasi, dokumentasi, dan wawancara terhadap dua informan inti serta satu informan pendukung yang mewakili perangkat desa, pengelola desa wisata, dan pelaku usaha. Analisis diarahkan pada empat dimensi pemberdayaan, yaitu dimensi sosial, ekonomi, budaya, dan lingkungan. Hasil penelitian menunjukkan bahwa pengembangan Desa Wisata Dayun mendorong partisipasi masyarakat melalui kegiatan Kelompok Sadar Wisata, pelatihan layanan wisata, pengembangan usaha lokal, dan pemanfaatan embung terpadu sebagai daya tarik edukatif dan rekreatif. Pada dimensi ekonomi, program ini membuka peluang bagi usaha mikro, pengolahan produk lokal, homestay, jasa pemandu, dan produk kreatif seperti batik bermotif semangka serta olahan semangka. Pada dimensi budaya, pengembangan wisata memperkuat visibilitas seni Melayu, keramahan lokal, dan identitas desa. Pada dimensi lingkungan, program ini mendorong kesadaran kebersihan, pengelolaan sumber daya air, dan pemanfaatan aset desa secara konservatif. Penelitian ini menyimpulkan bahwa desa wisata dapat menjadi strategi pemberdayaan yang efektif apabila masyarakat ditempatkan sebagai aktor aktif dalam perencanaan, pengelolaan, dan evaluasi.